2023
DOI: 10.1021/acs.jpcb.2c08604
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Theory of the Acidity of the Solution in the Lumina of Viruses and Virus-Like Particles

Abstract: Recently, Maassen et al. measured an appreciable pH difference between the bulk solution and the solution in the lumen of virus-like particles, self-assembled in an aqueous buffer solution containing the coat proteins of a simple plant virus and polyanions (Maassen, S. J.; et al. Small 2018, 14, 1802081). They attribute this to the Donnan effect, caused by an imbalance between the number of negative charges on the encapsulated polyelectrolyte molecules and the number of positive charges on the RNA binding doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Given the importance of Donnan theory for the electrostatics and electrokinetics of soft particles and soft macroscopic surfaces [62][63][64], the current work may be valuable to address the domain of validity of this theory, especially for biological particles under high salt concentration conditions where steric effects can be significant. In another context, binding of metal ions and protons to particulate organic matter is commonly evaluated by equilibrium Non-Ideal Competitive Adsorption (NICA)-Donnan model [65].…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of Donnan theory for the electrostatics and electrokinetics of soft particles and soft macroscopic surfaces [62][63][64], the current work may be valuable to address the domain of validity of this theory, especially for biological particles under high salt concentration conditions where steric effects can be significant. In another context, binding of metal ions and protons to particulate organic matter is commonly evaluated by equilibrium Non-Ideal Competitive Adsorption (NICA)-Donnan model [65].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent development, Muhren et al confirmed the applicability of the Donnan theory in predicting the local pH shift through the utilization of the Poisson-Boltzmann theory. 114 Both theoretical analyses and experimental studies suggest that the immobile charges of amino acid residues on the surface of capsid can induce an imbalanced charge distribution. This disparity could potentially influence the influx of positively charged protons, consequently leading to pH shifts.…”
Section: Local Ph Of Viral Capsidmentioning
confidence: 99%
“…107,112 In addition to the studies of pH in native VLPs, a comprehensive understanding of the physicochemical condition and personalized regulation of the local pH within viral capsids holds the potential to position VLPs as promising platforms for enhancing catalytic performance. 107,114…”
Section: Local Ph Of Viral Capsidmentioning
confidence: 99%